Evaluation of the Viability of Untreated Leiomyomas Using Computed Tomography–Detected Calcification Patterns. Issue 1 (7th January 2022) - Crane, Erin P.; Fenlon, Edward P.; Ascher, Susan M.; Balaji, Dhiksha; Siegelman, Evan S.
Abstract : Objective: To evaluate the relationship between computed tomography (CT)-detected calcification patterns and Magnetic Resonance Imaging (MRI) enhancement as a surrogate for viability in untreated uterine leiomyomas. Methods: We queried 2 university hospital databases to identify patients with: (1) at least 1 calcified leiomyoma on CT greater than 1 cm (2) contrast-enhanced MRI of the pelvis performed within 5 years of the CT, and (3) no prior history of uterine fibroid embolization (UFE). Computed tomography was used to analyze calcification pattern and contrast-enhanced MRI to analyze size and viability. Results: There were 12, 862 reports that fit the criteria. After exclusion, 50 patients with 74 calcified untreated leiomyomas were analyzed. Three calcification patterns were identified: rim (n = 22), diffuse (n = 9), and coarse either less than or greater than 50% (n = 43). Four of 22 (18%) of leiomyomas with rim calcification were viable. Three of 9 (33%) of leiomyomas with diffuse calcification were viable. All leiomyomas with coarse calcifications were viable, 43 of 43 (100%). Conclusions: Leiomyomas with coarse calcifications are viable, whereas the majority with rim or diffuse calcification are not. This information may be helpful when triaging symptomatic women to treatment.